Peran Worklife Balance dan Stres Kerja terhadap Kinerja Karyawan dengan Organizational Citizenship Behavior sebagai Variabel Mediasi - Miftahul Hikmah; Hendra Lukito (Jurnal Bisnis dan Manajemen, 2021)
The purpose of this study is to determine and analyze the effect of (1) Worklife balance on employee performance (2) Job Stress on employee performance (3) Worklife balance on OCB (4) Job Stress on OCB (5) OCB on employee performance (6) OCB as mediating role between Worklife balance and employee performance (7) OCB as mediating role between Job Stress and employee performance. The population in this study is employees of PT PLN (Persero) UP2B Sumbagteng, amounting to 50 people, with census techniques. Data analysis techniques using quantitative analysis with analysis tools SmartPLS 3.0. The results of this study found that: (1) Worklife Balance has a significant effect on employee performance (2) Job stress is contradictory and has a significant effect on OCB and employee performance (3) The magnitude of the effect of Worklife Balance on OCB is shown by the coefficient of determination R² of 0.261 or 26,1% (4) The magnitude of the influence of OCB on employee performance is shown by the coefficient of determination R² of 0.375 or 37,5% (5) Then there is also an indirect relationship with partial mediation by the OCB variable.